Drug interactions in elderly (Amirkola Health and Ageing Project) - Zahra Fath Tabar; Ahmadreza Moghadamnia; Ali Bijani; Seyyed Reza Hosseini; Ali Akbar Moghadamnia (Babol University of Medical Sciences, 2022)
Background: Due to physiological changes and co-existing chronic diseases, the elderly has to take various drugs with different mechanisms that may increase the risk of drug interactions and side effects of medications. This study was performed to evaluate the profile of drug interactions of Amirkola elderly patients. Methods: This cross-sectional descriptive-analytical study is part of the Amirkola Health and Ageing Project (AHAP) which was done during 2012-2013 (Amirkola, Babol, Iran). Initial data collection was done on 1616 persons of ages 60 and older by observing their prescribed drugs and those prepared by self-medications. Results: Drug interactions were detected in 31.7% (95% CI; 29.41, 33.95) of the drug prescriptions. This included 28% of mild, 63.3% of moderate and 8.7% of severe drug interactions. Cardiovascular drugs (64.4%) were the most frequent drugs that induced drug-interactions. According on Beer criteria 2015, 39.97% of the elderly medications were identified as "inappropriate medication". NSAIDs had the highest prevalence of inappropriate drugs. There was a significant relationship between female gender, having underlying disease, living alone, having insurance, and polypharmacy with obtained drug interaction results (p<0.05). Conclusion: The findings of the present study indicate considerable drug interactions among the elderly in Amirkola, which highlights the need for careful prescribing and using of drugs in the elderly.